High-carbon-sequestration low-carbon concrete for reinforced concrete prefabricated component and preparation method thereof

By using a large amount of slag powder, sand and gravel, fly ash and stone powder in low-carbon concrete, and adding Bacillus micro powder and substrate, the capture of carbon dioxide is accelerated and calcium carbonate is formed, which solves the problem of steel bar corrosion during the carbonization of low-carbon concrete, and significantly improves the carbon sequestration ability and mechanical properties of concrete.

CN119797848APending Publication Date: 2025-04-11CHINA CONSTR WESTERN CONSTR NORTH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510023010.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

When using low-carbon concrete, the carbonization process reduces the pH of the concrete, resulting in accelerated corrosion of the steel bars and reduced adhesion, which in turn damages the strength and durability of the concrete.

Method used

A large amount of slag powder, sand and gravel, fly ash and stone powder are used to replace some silicate cement, and Bacillus micro powder and Bacillus substrate are added to promote the dissolution of calcium ions and carbon dioxide capture, form calcium carbonate, and enhance the carbon sequestration ability of concrete. At the same time, add an appropriate amount of rubber latex to prevent corrosion of steel bars and accelerate the carbonization rate of concrete through specific curing steps.

Benefits of technology

It significantly improves the carbon sequestration ability and mechanical stability of concrete, ensures the compressive strength and split tensile strength of the prefabricated reinforced concrete components, and extends the service life of the components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797848A_ABST
    Figure CN119797848A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of concrete, and particularly discloses high-carbon-sequestration and low-carbon concrete for a reinforced concrete prefabricated component and a preparation method of the high-carbon-sequestration and low-carbon concrete. The invention relates to high-carbon-sequestration low-carbon concrete for a reinforced concrete prefabricated part. The high-carbon-sequestration low-carbon concrete is prepared from the following raw materials in parts by weight: 180-200 parts of Portland cement; 80 to 85 parts of slag powder; 1600 to 1800 parts of sand and stone; 80 to 100 parts of fly ash; 200 to 250 parts of stone powder; 20 to 25 parts of bacillus micro powder; 20 to 30 parts of a bacillus substrate; 150 to 200 parts of water; 5-10 parts of a water reducing agent; the preparation method comprises the following step: uniformly mixing the raw materials to prepare the high-carbon-sequestration low-carbon concrete. The low-carbon concrete has good mechanical stability and still has compact texture and excellent strength under multiple curing, the compressive strength is not lower than 89 MPa, and the splitting tensile strength is not lower than 9.93 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of concrete, and in particular to a high-carbon-fixed and low-carbon concrete for prefabricated reinforced concrete components and a preparation method thereof. Background Art

[0002] Concrete carbonation refers to the carbonation phenomenon of concrete during use. 2 The process of penetrating into concrete and reacting chemically with alkaline substances to produce carbonates and water, which reduces the alkalinity of concrete, is called concrete carbonation, also known as neutralization. Moderate carbonation can absorb carbon dioxide during the carbonization process of concrete and convert it into stable carbonates, which helps to reduce the carbon dioxide content in the atmosphere and has a positive impact on the environment. At the same time, a calcium carbonate protective layer is formed on the surface of concrete, which improves the density of concrete and reduces the penetration of moisture and harmful substances, thereby improving the durability and corrosion resistance of concrete.

[0003] On this basis, some researchers have proposed low-carbon concrete, which is a type of concrete that uses fly ash, slag, silica fume and other cementitious materials to replace cement. These cementitious materials have higher alkalinity, which means they have higher carbon fixation capacity and rate. Therefore, under the premise of ensuring the basic safety and durability of concrete, by using low-carbon emission materials, improving the utilization rate of solid waste and optimizing the production process, a high-performance, high-durability concrete with low CO2 emissions throughout its life cycle can be obtained. 2 However, it should be noted that the carbonization degree of concrete should not be too large, otherwise the texture of the concrete will become loose, resulting in a significant reduction in strength, which in turn affects the structural durability of the concrete.

[0004] Conventional concrete reinforcement methods include adding steel bars, chemical grouting, and adding external steel structures. Among them, adding steel bars can more significantly improve the bearing capacity, stability and durability of the structure. However, there are certain problems when this method is applied to low-carbon concrete. Since carbonization will reduce the pH value of concrete, this process will accelerate the corrosion of the steel bars. The expansion phenomenon and strength loss of the steel bars after corrosion will make it impossible for the steel bars to effectively improve the strength of the concrete. At the same time, the bonding strength between the corroded steel bars and the concrete will be reduced, which will cause damage to the concrete. Summary of the invention

[0005] In order to solve the above technical problems, the present application provides a high-carbon-fixed and low-carbon concrete for precast reinforced concrete components and a preparation method thereof.

[0006] In the first aspect, the present application provides a high-fixed carbon and low-carbon concrete for reinforced concrete prefabricated components, the raw materials used including the following components in parts by weight: 180-200 parts of silicate cement; 80-85 parts of slag powder; 1600-1800 parts of sand and gravel; 80-100 parts of fly ash; 200-250 parts of stone powder; 20-25 parts of Bacillus micropowder; 20-30 parts of Bacillus substrate; 150-200 parts of water; and 5-10 parts of water reducer.

[0007] Preferably, the raw materials used include the following components in parts by weight: 190 parts of silicate cement; 82 parts of slag powder; 1700 parts of sand and gravel; 90 parts of fly ash; 225 parts of stone powder; 23 parts of Bacillus micropowder; 25 parts of Bacillus substrate; 175 parts of water; and 7.5 parts of water reducer.

[0008] By adopting the above technical scheme, the present application adopts a large amount of slag powder, sand and gravel, fly ash and stone powder to replace part of the silicate cement, and adds bacillus powder and bacillus substrate, which greatly promotes the dissolution of calcium ions in slag powder, sand and gravel, fly ash and stone powder, and provides necessary calcium ions for bacillus powder and bacillus substrate. Bacillus powder and bacillus substrate accelerate the capture of carbon dioxide, mineralize and precipitate calcium ions to precipitate calcium carbonate, thereby improving the overall carbon fixation capacity of concrete, and the addition of bacillus powder and bacillus substrate can promote the carbonization products in the system to tend to calcite crystalline calcium carbonate, away from cubic crystalline calcium carbonate and spherical crystalline calcium carbonate, which means that the carbonization products in the concrete system of the present application have larger crystal size, smaller grain size and higher irregularity, have better mechanical stability, and still have dense texture and excellent strength under the multiple curing of the present application, with a compressive strength of not less than 89MPa and a splitting tensile strength of not less than 9.93MPa.

[0009] Preferably, the raw materials used also include rubber latex, which includes carboxylated nitrile emulsion and carboxylated styrene butadiene emulsion in a weight ratio of (93-100):(0-7), and the amount of rubber latex used is 2-4.5wt% of the amount of silicate cement used.

[0010] By adopting the above technical scheme, the present application adds rubber latex to the raw materials used, which can have a good anti-corrosion effect on steel bars, and the present application controls the amount of rubber latex added. If the amount added is too large, it will easily form a flocculent structure with silicate cement particles that is not conducive to flow. At the same time, the adsorption of silicate cement will also inhibit cement hydration and reduce the strength of reinforced concrete prefabricated components; if the amount added is too small, it will not have an effective anti-corrosion effect.

[0011] Preferably, the amount of the rubber latex is 4wt% of the amount of silicate cement.

[0012] By adopting the above technical scheme, the application strictly controls the amount of rubber emulsion to 4wt% of the amount of silicate cement. At this time, the anti-corrosion effect of the rubber emulsion is the best, and at the same time, it does not have a negative impact on the flow and hydration of the cement. According to experimental data, the compressive strength and splitting tensile strength of the reinforced concrete prefabricated components at this time reach 96.5MPa and 10.68MPa.

[0013] Preferably, the weight ratio of the carboxylated nitrile emulsion to the carboxylated styrene butadiene emulsion is 96:4.

[0014] By adopting the above technical scheme, the present application further controls the weight ratio of carboxylated nitrile emulsion and carboxylated styrene butadiene emulsion, thereby maximizing the extension of the vulcanization process of the rubber emulsion, achieving the effect of slow vulcanization and gradual penetration of the concrete system, thereby maximizing the anti-corrosion effect of the rubber emulsion. According to experimental data, the compressive strength and splitting tensile strength of the precast reinforced concrete components reached 99.3MPa and 10.92MPa.

[0015] In a second aspect, the present application provides a method for preparing high-carbon-fixed low-carbon concrete for reinforced concrete prefabricated components, comprising the following steps: mixing the raw materials used evenly to obtain high-carbon-fixed low-carbon concrete.

[0016] In a third aspect, the present application provides a method for preparing high-carbon-fixed low-carbon concrete for reinforced concrete prefabricated components, comprising the following steps: building a steel skeleton, then pouring the high-carbon-fixed low-carbon concrete into the steel skeleton, vibrating, curing, and demolding to obtain a reinforced concrete prefabricated component, in the curing step, first saturating Ca(OH) 2 Curing for 3 days, then autoclaving for 1 day, and then CO 2 After 3 days of curing, the steel precast concrete components are finally demoulded and naturally cured for 21 days.

[0017] Preferably, the saturated Ca(OH) 2 The temperature during curing is 25-35℃.

[0018] Preferably, the temperature during the autoclave curing is 180-210° C. and the pressure is 1.2-1.3 MPa.

[0019] Preferably, the CO 2 The curing temperature is 25-35℃, CO 2 The concentration is 25-30%.

[0020] By adopting the above technical solution, the present application builds a steel skeleton with steel bars. The amount of steel bars added and the shape of the steel skeleton can be adjusted according to actual needs. The cross-sectional diameter of the steel bars used in the present application is 12mm, the tensile strength is 200MPa, and the amount of steel bars added is 3% of the total volume. Then, the high-carbon-fixed low-carbon concrete is poured into the steel skeleton and vibrated. In addition to natural curing, the present application first performs saturated Ca(OH) 2 curing, then autoclaving, and finally CO 2 Maintenance and control of saturated Ca(OH) 2 The temperature during curing, the temperature and pressure during autoclave curing, and the CO 2 Temperature and CO during curing 2 The concentration accelerates the carbonation rate of concrete. Combined with the low cement dosage, Bacillus micropowder and Bacillus substrate of the present application, the strength of the system is guaranteed under the premise of increasing the carbon fixation amount and carbon fixation rate of concrete. The final reinforced concrete prefabricated components have excellent compressive strength and splitting tensile strength.

[0021] In summary, this application has the following beneficial technical effects: 1. The present application uses a large amount of slag powder, sand, fly ash and stone powder to replace part of the silicate cement, and adds bacillus powder and bacillus substrate, which greatly promotes the dissolution of calcium ions in slag powder, sand, fly ash and stone powder, and provides necessary calcium ions for bacillus powder and bacillus substrate. Bacillus powder and bacillus substrate accelerate the capture of carbon dioxide, mineralize and precipitate calcium ions to precipitate calcium carbonate, thereby improving the overall carbon fixation capacity of concrete, and the addition of bacillus powder and bacillus substrate can promote the carbonization products in the system to tend to calcite crystalline calcium carbonate, away from cubic crystalline calcium carbonate and spherical crystalline calcium carbonate, which means that the carbonization products in the concrete system of the present application have larger crystal size, smaller grain size and higher irregularity, have better mechanical stability, and still have dense texture and excellent strength under the multiple curing of the present application; 2. The present application adds rubber latex to the raw materials used, which can have a good anti-corrosion effect on steel bars, and the present application controls the amount of rubber latex added. If the amount added is too large, it will easily form a flocculent structure with silicate cement particles that is not conducive to flow. At the same time, the adsorption of silicate cement will also inhibit cement hydration and reduce the strength of reinforced concrete prefabricated components; if the amount added is too small, it will not have an effective anti-corrosion effect; 3. In the application of concrete, first saturate Ca(OH) 2 curing, then autoclaving, and finally CO 2 Maintenance and control of saturated Ca(OH) 2The temperature during curing, the temperature and pressure during autoclave curing, and the CO 2 Temperature and CO during curing 2 The concentration accelerates the carbonation rate of concrete. Combined with the low cement dosage, Bacillus micropowder and Bacillus substrate of the present application, the strength of the system is guaranteed under the premise of increasing the carbon fixation amount and carbon fixation rate of concrete. The final reinforced concrete prefabricated components have excellent compressive strength and splitting tensile strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 A schematic diagram of the steel reinforcement skeleton of the present application. DETAILED DESCRIPTION

[0023] Material Source Unless otherwise specified, the raw materials used in this application are all commercially available products, specifically: Portland cement was purchased from Tianjin Jinyu Zhenxing Environmental Protection Technology Co., Ltd., model P.O42.5; Slag powder was purchased from Lingshou County Zhan Teng Mineral Products Processing Plant, with an apparent density of 4.24 g / cm 3 , activity 99%; The sand and gravel were purchased from Nanyang Hengsheng Quartz Sand Filter Material Co., Ltd. The apparent density of the sand was 2600kg / m 3 , fineness modulus 3.1, medium sand in zone II; apparent density of stone 2730kg / m 3 , particle size range is 4.75-16mm; Fly ash was purchased from Shijiazhuang Zed Mineral Products Co., Ltd., with the model of F-II, fineness of 9.8%, and activity of 78%; The stone powder was collected from a machine-made sand processing plant in Lingshou County, Hebei Province. The particle size was measured to be 20±2μm; Bacillus micropowder was purchased from Hubei Haijia Biotechnology Co., Ltd.; Bacillus substrate was purchased from Anhui Zhuanpeptide Biotechnology Co., Ltd.; Polycarboxylic acid water reducer was purchased from Beijing Jinyu Cement Energy Saving Technology Co., Ltd., model JY-TS-1; Carboxylated nitrile emulsion was purchased from Kumho Petrochemical Co., Ltd., South Korea, with a solid content of about 44%; Carboxylated styrene butadiene emulsion was purchased from Rizhao Jinhu Jinma Chemical Co., Ltd., with a solid content of about 50%.

[0024] The present application is further described in detail below in combination with embodiments, application examples and comparative examples.

[0025] Example 1.1 A method for preparing high-carbon-fixed low-carbon concrete for reinforced concrete prefabricated components, comprising the following steps: mixing silicate cement, slag powder, sand and gravel, fly ash, stone powder, Bacillus powder, Bacillus substrate, water and polycarboxylic acid-based water reducer, and stirring for 10 minutes to obtain high-carbon-fixed low-carbon concrete. The specific amounts are shown in Table 1.1.

[0026] Table 1.1 Raw material dosage of Example 1.1 (kg) Example 1.2 A method for preparing high-carbon-fixed low-carbon concrete for reinforced concrete prefabricated components, comprising the following steps: mixing silicate cement, slag powder, sand and gravel, fly ash, stone powder, Bacillus micropowder, Bacillus substrate, water and polycarboxylic acid-based water reducer, and stirring for 10 minutes to obtain high-carbon-fixed low-carbon concrete. The specific amounts are shown in Table 1.2.

[0027] Table 1.2 Raw material dosage of Example 1.2 (kg) Components Example 1.2 Portland cement 200 Slag powder 80 Sand and gravel 1800 Fly ash 80 Stone powder 250 Bacillus powder 20 Bacillus substrate 30 water 150 Polycarboxylate water reducer 10 Example 1.3 A method for preparing high-carbon-fixed low-carbon concrete for reinforced concrete prefabricated components, comprising the following steps: mixing silicate cement, slag powder, sand and gravel, fly ash, stone powder, Bacillus powder, Bacillus substrate, water and polycarboxylic acid-based water reducer, and stirring for 10 minutes to obtain high-carbon-fixed low-carbon concrete. The specific amounts are shown in Table 1.3.

[0028] Table 1.3 Raw material dosage of Example 1.3 (kg) Example 2.1 A method for preparing high-carbon-fixed, low-carbon concrete for prefabricated reinforced concrete components, which is different from Example 1.3 in that 3.8 kg of carboxyl nitrile emulsion is also added, specifically: first, 175 kg of water, 7.5 kg of polycarboxylic acid-based water reducer and 190 kg of Portland cement are evenly mixed, stirred at a low speed for 3 minutes, and the carboxyl nitrile emulsion is added at a uniform speed within 3 minutes, and then 82 kg of slag powder, 1700 kg of sand and gravel, 90 kg of fly ash, 225 kg of stone powder, 23 kg of Bacillus powder and 25 kg of Bacillus substrate are added, stirring is continued for 2 minutes and then rapidly stirred for 5 minutes to obtain high-carbon-fixed, low-carbon concrete.

[0029] Example 2.2 A method for preparing high-carbon-fixed, low-carbon concrete for prefabricated reinforced concrete components, which is different from Example 1.3 in that 8.55 kg of carboxyl nitrile emulsion is also added, specifically: first, 175 kg of water, 7.5 kg of polycarboxylic acid-based water reducer and 190 kg of Portland cement are evenly mixed, stirred at a low speed for 3 minutes, and the carboxyl nitrile emulsion is added at a uniform speed within 3 minutes, and then 82 kg of slag powder, 1700 kg of sand and gravel, 90 kg of fly ash, 225 kg of stone powder, 23 kg of Bacillus powder and 25 kg of Bacillus substrate are added, stirring is continued for 2 minutes and then rapidly stirred for 5 minutes to obtain high-carbon-fixed, low-carbon concrete.

[0030] Example 2.3 A method for preparing high-carbon-fixed and low-carbon concrete for prefabricated reinforced concrete components, which is different from Example 1.3 in that 7.6 kg of carboxyl nitrile emulsion is also added, specifically: first, 175 kg of water, 7.5 kg of polycarboxylic acid-based water reducer and 190 kg of Portland cement are mixed evenly, stirred at a low speed for 3 minutes, and the carboxyl nitrile emulsion is added at a uniform speed within 3 minutes, and then 82 kg of slag powder, 1700 kg of sand and gravel, 90 kg of fly ash, 225 kg of stone powder, 23 kg of Bacillus powder and 25 kg of Bacillus substrate are added, stirring is continued for 2 minutes and then rapidly stirred for 5 minutes to obtain high-carbon-fixed and low-carbon concrete.

[0031] Example 2.4 A method for preparing high-carbon-fixed and low-carbon concrete for prefabricated reinforced concrete components, which differs from Example 2.3 in that 7.6 kg of carboxylated nitrile emulsion is replaced with 7.068 kg of carboxylated nitrile emulsion and 0.532 kg of carboxylated styrene butadiene emulsion, and the rest is the same as Example 2.3.

[0032] Example 2.5 A method for preparing high-carbon-fixed and low-carbon concrete for prefabricated reinforced concrete components, which differs from Example 2.3 in that 7.6 kg of carboxylated nitrile emulsion is replaced with 7.296 kg of carboxylated nitrile emulsion and 0.304 kg of carboxylated styrene butadiene emulsion, and the rest is the same as Example 2.3.

[0033] Example 2.6 A method for preparing high-carbon-fixed and low-carbon concrete for prefabricated reinforced concrete components, which differs from Example 2.3 in that 7.6 kg of carboxylated nitrile emulsion is replaced with 7.448 kg of carboxylated nitrile emulsion and 0.152 kg of carboxylated styrene butadiene emulsion, and the rest is the same as Example 2.3.

[0034] Comparative Example 1 The difference from Example 1.3 is that the Bacillus powder and the Bacillus substrate are removed, and the rest is the same as Example 1.3.

[0035] Comparative Example 2 The difference from Example 1.3 is that the Bacillus substrate is removed, and the rest is the same as Example 1.3.

[0036] Application Example 1 An application of high-carbon-fixed and low-carbon concrete for reinforced concrete prefabricated components comprises the following steps: S1. Build the steel frame: Figure 1 Build a steel skeleton in the shape shown, and design the size of the steel skeleton according to the amount of steel added being 3% of the total volume; S2, put the steel skeleton into the mold, and pour the high carbon fixation low carbon concrete obtained in Example 1.1 into the mold, vibrate until no bubbles are generated in the slurry, and then firstly in saturated Ca(OH) 2 Under the conditions of 25℃, saturated Ca(OH) 2 After curing for 3 days, the mixture was autoclaved at 180°C and 1.3 MPa for 1 day and then placed in CO 2 The CO concentration was 25% and the temperature was 35°C for 3 days. 2 After curing, the reinforced concrete precast components are finally naturally cured for 21 days and demoulding is performed to obtain the reinforced concrete precast components.

[0037] Application Example 2 An application of high-carbon-fixed and low-carbon concrete for reinforced concrete prefabricated components comprises the following steps: S1. Build the steel frame: Figure 1 Build a steel skeleton in the shape shown, and design the size of the steel skeleton according to the amount of steel added being 3% of the total volume; S2. Place the steel skeleton into a mold, pour the high carbon fixation low carbon concrete obtained in Example 1.2 into the mold, and vibrate until no bubbles are generated in the slurry. Then, firstly saturate the Ca(OH) 2 Under the conditions of 35℃, saturated Ca(OH) 2 After curing for 3 days, the mixture was autoclaved at 210°C and 1.2 MPa for 1 day and then placed in CO 2 The CO concentration was 30% and the temperature was 25°C for 3 days. 2 After curing, the reinforced concrete precast components are finally naturally cured for 21 days and demoulding is performed to obtain the reinforced concrete precast components.

[0038] Application Example 3 An application of high-carbon-fixed and low-carbon concrete for reinforced concrete prefabricated components comprises the following steps: S1. Build the steel frame: Figure 1 Build a steel skeleton in the shape shown, and design the size of the steel skeleton according to the amount of steel added being 3% of the total volume; S2, put the steel skeleton into the mold, and pour the high carbon fixed low carbon concrete obtained in Example 1.3 into the mold, vibrate until no bubbles are generated in the slurry, and then firstly in saturated Ca(OH) 2 Under the conditions of 30℃, saturated Ca(OH) 2 After curing for 3 days, the mixture was autoclaved at 195°C and 1.25 MPa for 1 day and then placed in CO 2 The CO concentration was 27.5% and the temperature was 30°C for 3 days. 2 After curing, the reinforced concrete precast components are finally naturally cured for 21 days and demoulding is performed to obtain the reinforced concrete precast components.

[0039] Application Example 4 An application of high-carbon-fixed, low-carbon concrete for prefabricated reinforced concrete components, which is different from Application Example 3 in that the high-carbon-fixed, low-carbon concrete prepared in Example 1.3 in step S2 is replaced by the high-carbon-fixed, low-carbon concrete prepared in Example 2.1, and the rest is the same as Application Example 3.

[0040] Application Example 5 An application of high-carbon-fixed low-carbon concrete for reinforced concrete prefabricated components, which is different from Application Example 3 in that the high-carbon-fixed low-carbon concrete prepared in Example 1.3 in step S2 is replaced by the high-carbon-fixed low-carbon concrete prepared in Example 2.2, and the rest is the same as Application Example 3.

[0041] Application Example 6 An application of high-carbon-fixed low-carbon concrete for reinforced concrete prefabricated components, which is different from Application Example 3 in that the high-carbon-fixed low-carbon concrete prepared in Example 1.3 in step S2 is replaced by the high-carbon-fixed low-carbon concrete prepared in Example 2.3, and the rest is the same as Application Example 3.

[0042] Application Example 7 An application of high-carbon-fixed low-carbon concrete for reinforced concrete prefabricated components, which is different from Application Example 3 in that the high-carbon-fixed low-carbon concrete prepared in Example 1.3 in step S2 is replaced by the high-carbon-fixed low-carbon concrete prepared in Example 2.4, and the rest is the same as Application Example 3.

[0043] Application Example 8 An application of high-carbon-fixed low-carbon concrete for reinforced concrete prefabricated components, which is different from Application Example 3 in that the high-carbon-fixed low-carbon concrete prepared in Example 1.3 in step S2 is replaced by the high-carbon-fixed low-carbon concrete prepared in Example 2.5, and the rest is the same as Application Example 3.

[0044] Application Example 9 An application of high-carbon-fixed low-carbon concrete for reinforced concrete prefabricated components, which is different from Application Example 3 in that the high-carbon-fixed low-carbon concrete prepared in Example 1.3 in step S2 is replaced by the high-carbon-fixed low-carbon concrete prepared in Example 2.6, and the rest is the same as Application Example 3.

[0045] Comparative application example 1 The difference from Application Example 3 is that in step S2, autoclave curing is first performed, and then saturated Ca(OH) 2 Maintenance, then CO 2 Curing, and finally natural curing, the rest is the same as application example 1.

[0046] Comparative Application Example 2 The difference from Application Example 3 is that in step S2, autoclave curing is performed first, and then CO 2 Maintenance, then saturated Ca(OH) 2 Curing, and finally natural curing, the rest is the same as application example 1.

[0047] Comparative Application Example 3 The difference from Application Example 3 is that in step S2, saturated Ca(OH) 2 Maintenance, then CO 2 Curing, then autoclaving and finally natural curing, the rest is the same as application example 3.

[0048] Comparative Application Example 4 The difference from Application Example 3 is that in step S2, CO 2 Curing, then autoclaving, then saturated Ca(OH) 2 Curing, and finally natural curing, the rest is the same as Application Example 3.

[0049] Comparative Application Example 5 The difference from Application Example 3 is that in step S2, CO 2 Maintenance, then saturated Ca(OH) 2 Curing, then autoclaving and finally natural curing, the rest is the same as application example 3.

[0050] Comparative Application Example 6 The difference from Application Example 3 is that the high-carbon-fixed low-carbon concrete prepared in Example 1.3 in step S2 is replaced by the high-carbon-fixed low-carbon concrete prepared in Comparative Example 1, and the rest is the same as Application Example 3.

[0051] Comparative Application Example 7 The difference from Application Example 3 is that the high-carbon-fixed low-carbon concrete prepared in Example 1.3 in step S2 is replaced by the high-carbon-fixed low-carbon concrete prepared in Comparative Example 2, and the rest is the same as Application Example 3.

[0052] Performance Testing According to the records in GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", different specimens were prepared by proportionally reducing the reinforced concrete precast components obtained in the application example. Cubes with a side length of 150 mm were made. Each group of specimens consisted of 3 pieces. The compressive strength (MPa) and splitting tensile strength (MPa) were tested. The average compressive strength and average splitting tensile strength of each group of 3 test pieces are recorded in Table 2.

[0053] Table 2 Performance test table Group Compressive strength / MPa Splitting tensile strength / MPa Application Example 1 89.6 9.98 Application Example 2 89.1 9.93 Application Example 3 92.6 10.20 Application Example 4 95.4 10.55 Application Example 5 95.7 10.58 Application Example 6 96.5 10.68 Application Example 7 98.2 10.85 Application Example 8 99.3 10.92 Application Example 9 98.0 10.83 Comparative application example 1 80.7 7.05 Comparative Application Example 2 82.3 7.22 Comparative Application Example 3 84.0 7.44 Comparative Application Example 4 81.6 7.18 Comparative Application Example 5 82.4 7.26 Comparative Application Example 6 70.6 6.08 Comparative Application Example 7 72.3 6.25 Data Analysis: As can be seen from Table 2, the compressive strength of Application Example 1-2 can reach 89.1-89.6 MPa, and the splitting tensile strength can reach 9.93-9.98 MPa, proving that the carbonized product in the concrete system of the present application has a larger crystal size, a smaller grain size and a higher degree of irregularity, has better mechanical stability, and still has a dense texture and excellent strength under the multiple curing of the present application; The compressive strength and splitting tensile strength of Application Example 3 are higher than those of Application Examples 1-2, proving that the present application can further improve the mechanical stability in the concrete system by controlling the proportion of each component; The compressive strength and splitting tensile strength of application examples 4-5 are much higher than those of application example 3, which proves that the application adds rubber latex to the raw materials used, which can have a good anti-corrosion effect on steel bars, and the application controls the amount of rubber latex added. If the amount added is too large, it will easily form a flocculent structure with silicate cement particles that is not conducive to flow. At the same time, the adsorption of silicate cement will also inhibit cement hydration and reduce the strength of reinforced concrete prefabricated components; if the amount added is too small, it will not have an effective anti-corrosion effect; The compressive strength and splitting tensile strength of Application Example 6 are higher than those of Application Examples 4-5, which proves that the application strictly controls the amount of rubber latex to 4wt% of the amount of Portland cement, at which time the anti-corrosion effect of the rubber latex is the best, and at the same time does not have a negative impact on the flow and hydration of cement; The compressive strength and splitting tensile strength of application examples 7-9 are higher than those of application examples 4-6, and the compressive strength and splitting tensile strength of application example 8 are the highest, which proves that the present application further controls the weight ratio of carboxylated nitrile emulsion and carboxylated styrene butadiene emulsion, thereby maximizing the extension of the vulcanization of the rubber emulsion, achieving the effect of slow vulcanization and gradual penetration of the concrete system, thereby maximizing the anti-corrosion effect of the rubber emulsion; The compressive strength and splitting tensile strength of application examples 1-7 are much lower than those of application example 3, which proves that the present invention firstly performs saturated Ca(OH) 2 curing, then autoclaving, and finally CO 2 Maintenance and control of saturated Ca(OH) 2 The temperature during curing, the temperature and pressure during autoclave curing, and the CO 2 Temperature and CO during curing 2 The concentration accelerates the carbonation rate of concrete. Combined with the low cement dosage, Bacillus micropowder and Bacillus substrate of the present application, the strength of the system is guaranteed under the premise of increasing the carbon fixation amount and carbon fixation rate of concrete. The final reinforced concrete prefabricated components have excellent compressive strength and splitting tensile strength.

[0054] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A high-carbon-fixed low-carbon concrete for reinforced concrete prefabricated components, characterized in that: The raw materials used include the following components in parts by weight: 180-200 parts of silicate cement; 80-85 parts of slag powder; 1600-1800 parts of sand and gravel; 80-100 parts of fly ash; 200-250 parts of stone powder; 20-25 parts of Bacillus micropowder; 20-30 parts of Bacillus substrate; 150-200 parts of water; 5-10 parts of water reducing agent.

2. The high-carbon-fixed low-carbon concrete for reinforced concrete prefabricated components according to claim 1, characterized in that: The raw materials used include the following components in parts by weight: 190 parts of silicate cement; 82 parts of slag powder; 1700 parts of sand and gravel; 90 parts of fly ash; 225 parts of stone powder; 23 parts of Bacillus micropowder; 25 parts of Bacillus substrate; 175 parts of water; 7.5 parts of water reducing agent.

3. The high-carbon-fixed low-carbon concrete for reinforced concrete prefabricated components according to claim 1, characterized in that: The raw materials used also include rubber emulsion, which includes carboxylated nitrile emulsion and carboxylated styrene butadiene emulsion in a weight ratio of (93-100): (0-7), and the amount of rubber emulsion is 2-4.5wt% of the amount of silicate cement.

4. The high-carbon-fixed low-carbon concrete for reinforced concrete prefabricated components according to claim 3, characterized in that: The amount of the rubber latex used is 4wt% of the amount of silicate cement used.

5. The high-carbon-fixed low-carbon concrete for reinforced concrete prefabricated components according to claim 3, characterized in that: The weight ratio of the carboxylated nitrile emulsion to the carboxylated styrene butadiene emulsion is 96:

4.

6. A method for preparing low-carbon concrete with high carbon fixation according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: the raw materials are mixed evenly to obtain low-carbon concrete with high carbon fixation.

7. An application of high-carbon-fixed low-carbon concrete for reinforced concrete prefabricated components, characterized in that: The following steps are involved: A steel skeleton is constructed, and then the high-carbon fixed low-carbon concrete is poured into the steel skeleton, and the precast reinforced concrete components are obtained after vibration, curing, and demolding. In the curing step, saturated Ca(OH)2 curing is first performed for 3 days, then autoclaving curing is performed for 1 day, CO2 curing is continued for 3 days, and finally natural curing is performed for 21 days, and demolding is performed to obtain the precast reinforced concrete components.

8. The use of high-carbon-fixed and low-carbon concrete for reinforced concrete prefabricated components according to claim 7, characterized in that: The temperature during the saturated Ca(OH)2 curing is 25-35°C.

9. The use of high-carbon-fixed and low-carbon concrete for reinforced concrete prefabricated components according to claim 7, characterized in that: The temperature during the autoclave curing is 180-210° C. and the pressure is 1.2-1.3 MPa.

10. The use of high-carbon-fixed and low-carbon concrete for reinforced concrete prefabricated components according to claim 7, characterized in that: The temperature during the CO2 curing is 25-35°C, and the CO2 concentration is 25-30%.